PENERAPAN KETERAMPILAN DASAR DALAM KONSELING KELOMPOK OLEH GURU BK DI KELAS VIII - Putri, Yosi Eka (Bimbingan dan Konseling, 2014)
The problem that be thorough grounded on the phenomenon in the field, that is in counseling activity group has been found the guidance and counseling teachers that still have applyyet the basic skill in the counseling activity group, like speaking active, reflection, eye contact, encouragement and backing, that make participant education fell. Difficult to express the problem. The purpose of this research are to describe: 1) applying listening skil, 2) reflection, 3) encouragemen and backing, 4) eye contact in counseling group. This research is descriptive research. The population of this research are the participant education of junior high school 31 padang counseling group amount of 32 peoples. The technique of taking sample is purposive sampling. The instrument that is used in this research is questionnaire, whereas to data analyze used percentage technigue. The result of this research show that: 1) application of listening skil, 2) reflection, 3) eye contact, 4) encouragement and backing by the guidance and counseling theacher in the good criteria.